Kontroversi Akhbârî-Ushûlî dalam Tradisi Pemikiran Syî‘Ah Imâmiyyah - Rusli Rusli (Ulumuna, 2009)
This paper deals with the controversy that occurs between Akhbârî and Ushûlî within Syî’ah Imâmiyyah’s thought. The controversy lies on the legal methodology employed in understanding the will of God after the great occultation of the twelfth Imam. Akhbâri, which is literalist in nature, tends to absolutely get rid of reason as a means of deriving Islamic laws, while insists on revelation and akhbâr of the Imams. They strictly hold that Shi’ites must absolutely follow such twelve imams, since it is only they who are able to accurately interpret the Quran. On the other hand, Ushûlî allow the use of ijtihâd (legal reasoning) into a great deal in making legal decisions, and also argue that a Shi’ite must abide by mujtahid (legal experts), as well as the Imams. Therefore, they can come up with vital concepts in a religious life of Shi’ites nowadays, such as marja‘ al-taqlîd and wilâyat al-faqîh